Penyuluhan Hukum Tentang Penguatan Pemahaman Kode Etik Profesi Guru di SMAN 1 Luwuk - Irzha Friskanov. S; Dewi Kemala Sari; Widyatmi Anandy; Adiguna Kharismawan; Bambang Hermawan (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2026)
Legal counseling activities on strengthening understanding in the teacher professional code of ethics aim to increase teachers’ awareness and understanding of legal aspects that regulate responsibilities, rights, obligations, and consequences of violations of the professional code of ethics. Lack of understanding of legal regulations often leads to ethical violations that have an impact on the professionalism and image of teachers as educators. Therefore, this activity provides comprehensive and applicable knowledge through several methods, problem identification, interactive discussion counseling, case simulation, and evaluation and follow-up. This service activity was carried out at SMA Negeri 1 Luwuk which was attended by 25 teachers as participants. The main achievements of this activity include increasing teachers’ understanding of the code of ethics and its legal aspects, the establishment of a legal consultation forum for teachers, and reducing the potential for violations in the school environment. With this activity, it is hoped that teachers will be able to apply the code of ethics professionally, understand the legal consequences of violations, and build a strong legal culture in the educational environment. This counseling is a concrete step in creating an educational environment with integrity, accountability, and in accordance with applicable legal norms.